Analysis of eEF1A2 gene expression and copy number in cervical carcinoma. Issue 2 (13th January 2023) - Zheng, Weinan; Jin, Fuyuan; Wang, Fang; Wang, Luyue; Fu, Shaowei; Pan, Zemin; Long, Haichen
Abstract : Objective: To explore and analyze the expression of eukaryotic translation elongation factor 1 alpha 2 ( eEF1A2 ) gene in cervical cancer tissues, its relationship with patient survival, gene mutations, and changes in copy number in cervical cancer and chronic cervicitis tissues. Methods: The expression of the eEF1A2 gene in cervical cancer and its relationship with patient survival were analyzed using gene expression profile interactive analysis. Changes in eEF1A2 expression in cervical cancer tissues were analyzed using cBioPortal, a portal for cancer genomics analysis. The eEF1A2 copy number in cervical cancer tissues and chronic cervicitis tissues was determined by real-time fluorescence quantitative polymerase chain reaction. The relationship between the expression of eEF1A2 protein and the clinical stage, pathological grade, and patient survival of cervical cancer was analyzed by the database: The Human Protein Atlas, an integrated repository portal for tumor-immune system interactions. Results: Gene expression profile interactive analysis database analysis showed no significant differences in the expression of eEF1A2 between cervical cancer and normal cervical tissues ( P > .05). The eEF1A2 gene expression level was not correlated with the survival of cervical cancer patients ( P > .05). Analysis of the cBioPortal database showed that 18 of 297 cervical cancer patients had eEF1A2 gene changes, including missense mutation, splice mutation, amplification, and messenger RNA increase. There was no significant difference in eEF1A2 gene copy number between cervical cancer and chronic cervicitis ( P > .05). The Human Protein Atlas and an integrated repository portal for tumor-immune system interactions database analysis of immunohistochemical data showed that eEF1A2 protein expression was no significant difference in clinical stage, pathological grade and patient survival of cervical cancer ( P > .05). Conclusion: The eEF1A2 gene was mutated in cervical cancer tissues. The eEF1A2 gene copy number was not associated with changes in the expression of the eEF1A2 gene in cervical cancer tissues.